1994
DOI: 10.1128/aem.60.12.4634-4637.1994
|View full text |Cite
|
Sign up to set email alerts
|

Trichloroethylene removal and oxidation toxicity mediated by toluene dioxygenase of Pseudomonas putida

Abstract: Whole cells of Pseudomonas putida containing toluene dioxygenase were able to remove all detectable trichloroethylene (TCE) from assay mixtures. The capacity of cells to remove TCE was 77 ,uM/mg of protein with an initial rate of removal of 5.2 nmol/min/mg of protein. TCE oxidation resulted in a decrease in the growth rate of cultures and caused rapid cell death. Addition of dithiothreitol to assay mixtures increased the TCE removal capacity of cells by up to 67% but did not prevent TCE-mediated cell death. TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(14 citation statements)
references
References 15 publications
(13 reference statements)
2
12
0
Order By: Relevance
“…An additional objective of this study was to confirm and expand upon the recent findings that Heald and Jenkins (21) obtained with P. putida and that McClay et al (35) obtained with P. mendocina KR1 and Pseudomonas sp. strain ENVPC5 which showed that TCE can act as an inducer of tolueneoxidizing activity.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…An additional objective of this study was to confirm and expand upon the recent findings that Heald and Jenkins (21) obtained with P. putida and that McClay et al (35) obtained with P. mendocina KR1 and Pseudomonas sp. strain ENVPC5 which showed that TCE can act as an inducer of tolueneoxidizing activity.…”
supporting
confidence: 61%
“…Trichloroethylene (TCE), a suspected carcinogen (43) and U.S. Environmental Protection Agency priority pollutant (60), is the most commonly reported volatile organic contaminant of groundwater (51). TCE can be degraded by means of a cooxidation reaction which has been shown to be catalyzed by both toluene dioxygenase (9,21,68) and monooxygenase (29,55,66) enzyme systems found in toluene-oxidizing bacteria. Linkage of TCE degradation with the metabolism of aromatic hydrocarbons has been established for indigenous microbial populations in soil (11,13,42) and groundwater (22)(23)(24), in which TCE removal has been shown to be stimulated by the addition of toluene or phenol.…”
mentioning
confidence: 99%
“…The difference in growth or no growth is dependent solely on the genetic regulation of toluene 2-monooxygenase. In this context, it is of interest that TCE induces the expression of toluene dioxygenase in Pseudomonas putida UV4 (7) and of toluene 4-monooxygenase in Pseudomonas mendocina KR1 (14). These results and those of the present study highlight the importance of matching enzyme and induction specificities for optimizing the metabolic capabilities of organisms.…”
supporting
confidence: 65%
“…Trichloroethylene, a suspected carcinogen and U.S. Environmental Protection Agency priority pollutant, is a common groundwater and soil contaminant in the United States. Various types of aerobic bacteria, including methanotrophs [1–3], toluene oxidizers [4,5], phenol oxidizers [6], and ammonia oxidizers [1], have been shown to cometabolically degrade TCE. Growth of these bacteria on substrates other than chlorinated aliphatic compounds involve nonspecific oxygenase enzymes that are able to fortuitously degrade these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Growth of these bacteria on substrates other than chlorinated aliphatic compounds involve nonspecific oxygenase enzymes that are able to fortuitously degrade these compounds. In toluene‐degrading microorganisms, for example, TCE can be degraded by means of both dioxygenase [4,5,7,8] and mono‐oxygenase [9] enzyme systems. The relationship between cometabolic TCE transformation and toluene consumption has been described qualitatively by many researchers over the past decade [5,10–15].…”
Section: Introductionmentioning
confidence: 99%